Agri-environmental Schemes Require Improved Design for Better Outcomes - Chi Nguyen; Uwe Latacz-Lohmann; Nick Hanley (EuroChoices, 2024)
Advocacy for a shift from an individual farm-level to a landscape-level approach in agri-environmental policy is a focal point in the reform of the Common Agricultural Policy. Such a shift aims to address spatial mismatches between ecological processes and targeted environmental outcomes, and to harness potential ecological gains from spatial coordination. However, there remains limited understanding of how to design effective mechanisms aimed at encouraging coordination among landholders. Do landscape configurations influence the effectiveness of coordination mechanisms? This article aims to assess the effectiveness of alternative coordination mechanisms incorporated in the design of a conservation auction across alternative landscape configurations, that is, in terms of the spatial relationship between some measure of environmental benefit – such as wild bird species diversity – and the profitability of farmland. These mechanisms include landholder-to-landholder communication, disclosure of spatial environmental scoring rules, and the Agglomeration Bonus. We used lab experiments to evaluate these options. Our results suggest that there is no panacea for promoting landscape-level environmental outcomes. Communication proves capable of significantly facilitating coordination, whilst information disclosure policies can serve as an effective coordination mechanism in multiple landscape types. By contrast, the Agglomeration Bonus was only found to effectively promote coordination in a positively correlated landscape type. It leads to lower cost-effectiveness in all landscape types. – – Ein Schwerpunkt der Reform der Gemeinsamen Agrarpolitik ist das Befürworten einer Verlagerung von einem individuellen zu einem landschaftsbezogenen Ansatz in der Agrarumweltpolitik. Eine solche Verlagerung soll räumliche Missverhältnisse zwischen ökologischen Prozessen und angestrebten Umweltergebnissen angehen und potenzielle ökologische Vorteile einer räumlichen Koordinierung nutzen. Es gibt jedoch kaum Erkenntnisse darüber, wie Mechanismen zur Förderung der Koordinierung zwischen Landbesitzenden wirksam gestaltet werden können. Beeinflusst die Konfiguration der Landschaft die Wirksamkeit der Koordinierungsmechanismen? Das Ziel dieses Artikels ist es, die Wirksamkeit alternativer Koordinationsmechanismen zu bewerten, die in das Design einer Naturschutzauktion über verschiedene Landschaftskonfigurationen hinweg integriert wurden, definiert hinsichtlich der räumlichen Korrelation zwischen Umweltnutzen und Opportunitätskosten. Diese Mechanismen umfassen die Kommunikation zwischen den Landbesitzenden, die Offenlegung der Bestimmungen der räumlichen Umweltbewertung und den Agglomerationsbonus. Wir haben diese Optionen in Laborexperimenten bewertet. Unsere Ergebnisse deuten darauf hin, dass es kein Allheilmittel zur Förderung von Umweltergebnissen auf Landschaftsebene gibt. Kommunikation erweist sich als geeignet, die Koordinierung erheblich zu erleichtern, während eine Politik der Offenlegung von Informationen als wirksamer Koordinierungsmechanismus bei verschiedenen Landschaftstypen dienen kann. Im Gegensatz dazu wurde festgestellt, dass der Agglomerationsbonus die Koordinierung nur bei einem einzigen Landschaftstyp wirksam fördert. Er führt bei allen Landschaftstypen zu einer geringeren Kosteneffizienz.
Keywords: 630